2022
DOI: 10.1186/s40545-022-00431-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pharmacist services on economic, clinical, and humanistic outcome (ECHO) of South Asian patients: a systematic review

Abstract: Background Pharmacists in high-income countries routinely provide efficient pharmacy or pharmaceutical care services that are known to improve clinical, economic, and humanistic outcomes (ECHO) of patients. However, pharmacy services in low- and middle-income countries, mainly South Asia, are still evolving and limited to providing traditional pharmacy services such as dispensing prescription medicines. This systematic review aims to assess and evaluate the impact of pharmacists’ services on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 57 publications
(111 reference statements)
0
18
0
Order By: Relevance
“…Basing on the definition from ECHO model for the clinical, economic and humanistic outcomes ( Cheng et al, 2013 ; Shrestha et al, 2022 ; Gunter., 2023 ), the definition of outcomes included in our study was confirmed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Basing on the definition from ECHO model for the clinical, economic and humanistic outcomes ( Cheng et al, 2013 ; Shrestha et al, 2022 ; Gunter., 2023 ), the definition of outcomes included in our study was confirmed.…”
Section: Methodsmentioning
confidence: 99%
“…Although several studies comprehensively evaluated patient’s burden and medical interventions using the ECHO model, such as refill adherence measures and STOPP/START criteria ( Reeder et al, 2000 ; Jeremy et al, 2011 ; Hill-Taylor et al, 2013 ; Zhao et al, 2019 ; Chua et al, 2020 ), few studies evaluated the efficacy of MTM services with full ECHO model. Despite descriptive studies demonstrating that MTM services improved patients’ clinical conditions, quality of life and potentially reduced healthcare disparities ( Bunting and Cranor, 2006 ; Shrestha et al, 2022 ), studies analyzed the three parts of ECHO model in one assessment was little ( Singhal et al, 1999 ; Cheng et al, 2013 ; Johnson et al, 2018 ). The incompleteness of the analysis may result in superficial conclusions and less precise outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Drug information service is one of the pharmaceutical services that can improve clinical outcomes in T2DM. Drug information service is a part of pharmaceutical care delivered in public health centers and other settings like hospitals or pharmacies 13 . Drug information service is defined as a service by pharmacists to provide accurate, precise, and up-to-date information to doctors, pharmacists, other health professionals, and patients.…”
Section: Effect Of Drug Information Service On Clinical Outcome Of Pa...mentioning
confidence: 99%
“…The impact of pharmacist interventions resulted in medication cost savings of US$3million over 10 years and the improvement of the conditions of 55% of patients ( Oliveira et al, 2010 ). A systematic review conducted in Southeast Asia to evaluate the impact of pharmacist services on economic, clinical and humanistic outcomes ( Shrestha et al, 2022 ). Therapeutic outcomes such as HbA1c level and blood pressure were improved, as were humanistic outcomes such as adherence to prescription instructions, knowledge regarding medication and quality of life ( Shrestha et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%